The bank´s role as financial intermediary for the acquisition of real estate within the framework of real estate project development - Arteaga Reátegui, Mónica Jeanette (2024)
The purpose of this article is to enable the reader to understand the context in which a real estate project is developed, the existing financing alternatives, the legal relationships that arise in connection with it, as well as the various events that may occur and affect the end consumers.For the analysis of this context, the bank will be a fundamental actor, since its role in the development of these real estate projects is not limited only to being a financial agent, but, in fact, it plays an active control role that will extend until the completion of the project. Notwithstanding the active role played by the bank, it is considered that it should not be held responsible for any event that may interrupt the normal development of the real estate project, proposing as an alternative for the protection of the end consumer, the constitution of an escrow deposit.